2004
DOI: 10.1158/0008-5472.can-04-0401
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Vascular Endothelial Growth Factor (VEGF) as a Surrogate Marker for Optimal Therapeutic Dosing of VEGF Receptor-2 Monoclonal Antibodies

Abstract: A major obstacle compromising the successful application of many of the new targeted anticancer drugs, including angiogenesis inhibitors, is the empiricism associated with determining an effective biological/therapeutic dose because many of these drugs express optimum therapeutic activity below the maximum tolerated dose, if such a dose can be defined. Hence, surrogate markers are needed to help determine optimal dosing. Here we describe such a molecular marker, increased plasma levels of vascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 34 publications
(33 reference statements)
12
119
2
2
Order By: Relevance
“…Our observations are consistent with recent studies by Bocci et al (27), which reported that plasma VEGF levels are normally very low or undetectable, but are rapidly increased upon treatment with blocking VEGFR2 antibodies. In these experiments, the observed acute increase in circulating VEGF was not associated with increased VEGF expression in normal tissues, or the tumors, but reflected displacement of VEGF from VEGF receptors.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are consistent with recent studies by Bocci et al (27), which reported that plasma VEGF levels are normally very low or undetectable, but are rapidly increased upon treatment with blocking VEGFR2 antibodies. In these experiments, the observed acute increase in circulating VEGF was not associated with increased VEGF expression in normal tissues, or the tumors, but reflected displacement of VEGF from VEGF receptors.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the individual plasma VEGF concentrations of patients initially increased when compared to the baseline values in the first 3 weeks and then at lower doses constantly decreased. Despite the presence of a high variability, VEGF plasma levels may reflect both the initial elevated hypoxia of tumour tissue caused by the antiangiogenic therapy, as previously shown (Bocci et al, 2004;Motzer et al, 2006), and the low rate of VEGF secretion by tumour or tumourassociated stromal cells due to the long-term therapy (Colleoni et al, 2002). This PK/PD study underlines the importance to conduct further comparative studies with BSC or bevacizumab to establish the feasibility of metronomic irinotecan approach.…”
Section: Discussionmentioning
confidence: 60%
“…Plasma levels of VEGF and placental-derived growth factor (PlGF, a VEGF family member that specifically binds to VEGF receptor 1) are significantly increased in rectal cancer patients receiving bevacizumab [46]. In apparent contrast to some preclinical findings [56], other groups have reported similar observations in cancer patients treated with various anti-VEGF receptor TKIs (e.g. vatalanib and sunitinib), and have also found a decrease in soluble VEGF receptor 2 levels in the plasma [57][58][59].…”
Section: Biomarkers Of Anti-vegf Therapymentioning
confidence: 95%